Formulation and characterization of polyherbal anti-acne gel containing Citrus aurantifolia and Aloe barbadensis extracts for the management of acne vulgaris - Hin, K.F.; Yusof, Y.A.; Salim, N.; Mohd Amin, N.A.A. (Rynnye Lyan Resources, 2023)
The antibiotic used to treat acne may develop antibiotic resistance and side effects. Meanwhile, treating acne-causing bacteria by applying Citrus aurantifolia juice to the skin immediately is ineffective. Citrus aurantifolia juice was employed in an anti-acne gel formulation to treat acne that was caused by Cutibacterium acnes and Staphylococcus epidermidis has no synergistic therapeutic effect shown. Additionally, polyherbal formulations are currently in high demand in the global market. The herbal industry's global market value has risen dramatically from US$60 billion in 2000 to US$105 billion in 2017. The worldwide market will increase at a rate of 7.6% each year until it reaches $5 trillion in 2050. This study aims to formulate a polyherbal anti-acne gel containing C. aurantifolia and Aloe barbadensis, and to characterize the formulated gel for its physicochemical properties. The phytoconstituents found in plant extracts were also analysed. The antibacterial activity of plant extracts against Staphylococcus aureus was also investigated using an agar well diffusion method. After plant extracts were discovered, gels with varying concentrations of plant extracts, and excipients were prepared along with compatibility studies. Parameters like colour, odour, homogeneity, phase separation, consistency, washability, pH, viscosity, spreadability and antibacterial activity were evaluated. The results showed that the levels of phenol, tannins, and flavonoids in plant extracts varied, the antibacterial activity of plant extracts was studied with a clear inhibition zone demonstrated, and plant extracts were compatible with all excipients. Gel formulations containing C. aurantifolia, A. barbadensis, the excipients Carbopol-940, methylparaben, propyl paraben, propylene glycol-400, triethanolamine and water have been developed. The formulated gels were clear, odourless, uniform, consistent, without lumps, and washable. It was found that pH was closer to the skin, good viscosity and spreadability. The formulated gel, F4 has greater antibacterial activity than plant extracts and other formulations with a larger diameter inhibition zone. It is concluded that the polyherbal anti-acne gel containing C. auranfolia and A. barbadensis can be formulated which has a high potential for halal cosmetics product development. However, more research should be done before it can be commercialised by comparing it to commercially available marketed formulations to treat acne vulgaris.